Lion's share : remaking South African copyright - Erlmann, Veit (Duke University Press, 2022)
"In the aftermath of apartheid, South Africa undertook an ambitious revision of its intellectual property system. In Lion's Share Veit Erlmann traces the role of copyright law in this process and its impact on the South African music industry. Although the South African government tied the reform to its post-apartheid agenda of redistributive justice and a turn to a post-industrial knowledge economy, Erlmann shows how the persistence of structural racism and Euro-modernist conceptions of copyright threaten the viability of the reform project. In case studies ranging from anti-piracy police raids and the crafting of legislation to protect indigenous expressive practices to the landmark lawsuit against Disney for its appropriation of Solomon Linda's song "The Lion Sleeps Tonight" for The Lion King, Erlmann follows the intricacies of musical copyright through the criminal justice system, parliamentary committees, and the offices of a music licensing and royalty organization. Throughout, he demonstrates how copyright law is inextricably entwined with race, popular music, postcolonial governance, indigenous rights, and the struggle to create a more equitable society."--